2014
DOI: 10.18406/2316-1817v7n12015544
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico e comportamento de cultivares de morangueiro quanto à mancha-de-Pestalotiopsis e às podridões dos frutos

Abstract: O cultivo do morangueiro desempenha uma importante função econômica e social, contribuindo para a geração de renda e melhoria da qualidade de vida, além da fixação do homem no campo. Embora as condições climáticas na região sul de Minas Gerais sejam favoráveis ao desenvolvimento da cultura, contribuem também para a maior incidência de doenças, sendo a mancha-de-pestalotiopsis uma das principais doenças fúngicas que pode causar sérios prejuízos aos produtores de morango. Objetivou-se, por meio deste trabalho, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
0
2
Order By: Relevance
“…The yield of the Albion variety of strawberry was similar to that obtained in a previous monocrop study in Dois Vizinhos, PR, County, in which values ranged from 319.50 to 386.50 g per plant (MAZARO et al, 2013) and were inferior compared to that obtained in Guarapuava in first cycle (784.3 g per plant) (ZEIST et al, 2019). For the Camarosa variety, similar yields were observed in studies conducted in Pouso Alegre -MG (137 g per plant) (PÁDUA et al, 2015) and Curitiba, PR Counties (117.70 g per plant) (LEMINSKA et al, 2014) and were inferior compared to that obtained in Guarapuava in first and second cycles (482.0 and 410.7 per plant for first and second cycles, respectively) (ZEIST et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…The yield of the Albion variety of strawberry was similar to that obtained in a previous monocrop study in Dois Vizinhos, PR, County, in which values ranged from 319.50 to 386.50 g per plant (MAZARO et al, 2013) and were inferior compared to that obtained in Guarapuava in first cycle (784.3 g per plant) (ZEIST et al, 2019). For the Camarosa variety, similar yields were observed in studies conducted in Pouso Alegre -MG (137 g per plant) (PÁDUA et al, 2015) and Curitiba, PR Counties (117.70 g per plant) (LEMINSKA et al, 2014) and were inferior compared to that obtained in Guarapuava in first and second cycles (482.0 and 410.7 per plant for first and second cycles, respectively) (ZEIST et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Greater production was obtained by Godoi et al (2009), with a total of 934.7 g plant -1 in bags and closed systems. In this work, the commercial fruit yields were higher than those found by Pádua et al (2015), in which values of 81.78 and 81.24 g plant -1 were measured for Camarosa and Albion, respectively.…”
Section: Effects Of Cultivar Origin Of the Transplants And Substratecontrasting
confidence: 72%
“…In the present study, high production of noncommercial fruits (PFNC) was observed for both Camarosa and Albion (9.2 and 11.3 g plant -1 , respectively). Pádua et al (2015) observed lower masses of non-commercial fruits than did the present study (6 g plant -1 ), and Duarte Filho, (2005) observed averages of 20 g plant -1 . Oliveira and Scivittaro (2009) observed heavier fruits in plants of Imported origin than in those of National origin.…”
Section: Effects Of Cultivar Origin Of the Transplants And Substratecontrasting
confidence: 59%